Chlorophylls and carotenoids of kiwifruit puree are affected similarly or less by microwave than by conventional heat processing and storage. (15th November 2015) - Benlloch-Tinoco, María; Kaulmann, Anouk; Corte-Real, Joana; Rodrigo, Dolores; Martínez-Navarrete, Nuria; Bohn, Torsten
Highlights: Effect of microwaves, heat processing and storage on kiwifruit pigments was studied. Impact of processing and storage on bioaccessibility of carotenoids was assessed. Neither processing nor storage influenced bioaccessibility of kiwifruit carotenoids. Processing helped to mitigate degradation of kiwifruit pigments over time. Chlorophylls were preserved better by microwaves than the conventional heat process. Abstract: The impact of microwave (1000 W – 340 s) and conventional heat (97 °C – 30 s) pasteurisation and storage (4, 10, 22 °C for up to 63 d) on total and individual carotenoids and chlorophylls in kiwifruit puree was evaluated. Bioaccessibility of carotenoids, before and after pasteurisation and storage, was also studied. Microwaves and conventional heating led to marked changes in the chlorophyll (42–100% losses) and carotenoid (62–91% losses) content. First- and second-order kinetics appropriately explained the degradation of total carotenoids and chlorophylls over time, respectively. Pasteurised samples showed significantly ( p < 0.05) enhanced stability of these pigments, with microwaves ( k = 0.007–0.031 100 g mg −1 day −1 at 4–22 °C) promoting chlorophyll stability to a greater extent than conventional heating ( k = 0.0015–0.034 100 g mg −1 day −1 at 4–22 °C). Bioaccessibility of carotenoids remained ( p < 0.05) unaffected by processing and storage. These results highlighted that the pigment composition of microwaved kiwifruit was more similar to that of the fresh fruit and better preserved during storage.